AB0138 Time-Course of Microvascular versus Macrovascular Endothelial Dysfunction in Rat Adjuvant-Induced Arthritis. (10th June 2014) - Totoson, P.; Maguin-Gaté, K.; Nappey, M.; Prati, C.; Wendling, D.; Demougeot, C.
Abstract : Background: Rheumatoid arthritis (RA) is associated with increased risk for cardiovascular disease (CVD). Whereas ample evidence demonstrated the presence of endothelial dysfunction (ED) in RA, it is still unclear how early this abnormality develops. Moreover most of studies have been performed on the macrovasculature but little is known about ED in the microvasculature. Objectives: The aim of this study is to investigate the time-course of microvascular and macrovascular impairment in adjuvant-induced arthritis (AIA) in rats. Methods: AIA was induced by an intradermal injection of Mycobacterium butyricum in the tail of male Lewis rats (Day 0). Arthritis severity was evaluated by clinical and radiological analysis at 4 stages of AIA: day 4 (preclinical stage), day 11 (very early arthritis), day 33 (severe disease), day 90 (chronic disease). At each stage, functional and mechanical properties of third-order mesenteric arteries were determined by assessing flow-mediated dilatation, myogenic tone and stress-strain relationship. Macrovascular function was studied on isolated aortic rings in which the contractile response to norepinephrine (NE) and the vasorelaxant response to Acetylcholine (Ach) and to sodium nitroprussiate (SNP) were evaluated. Results: Macrovascular ED became evident at the severe disease. At the chronic phase of AIA the presence of ED was positively correlated to the radiological score. The response of aortic rings to SNP was normal whatever the stage of AIA. By contrast, NE-induced contractility was significantly reduced in AIA at day 4, and recovered the normal values thereafter. In microvascular bed, ED appears at the early arthritis stage. At the severe disease, microvascular ED is still present and is associated with reduced arterial stiffness. At day 90, one group of microvessels from AIA exhibited ED whereas another group did not, but ED was not correlated to the radiological score. Myogenic tone was unchanged during the course of arthritis. Conclusions: Our results demonstrated that micro and macrovascular beds are differentially affected during the course of RA. Microvascular ED is a very early event in the course of arthritis. It precedes the occurrence of macrovascular ED and microvascular stiffness. Our data suggest that the measurement of microvascular function would be relevant for the early diagnosis of CV risk in RA patients. They also suggest that mechanisms underlying macro- and microvascular dysfunction are different. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.1687